SUMOylation determines turnover and localization of nephrin at the plasma membrane - Tossidou, Irini; Himmelseher, Erik; Teng, Beina; Haller, Hermann; Schiffer, Mario (Kidney International, 2014)
Podocyte effacement and the reformation of foot processes and slit diaphragms can be induced within minutes experimentally. Therefore, it seems likely that the slit diaphragm proteins underlie orchestrated recycling mechanisms under the control of posttranslational modifiers. One of these modifiers, SUMO (small ubiquitin-like modifier), is an ubiquitin-like protein with a 20% corresponding identity to ubiquitin. Modification by SUMOs to proteins on lysine residues can block the ubiquitination of the same site leading to the stabilization of the target protein. Here we found in vitro and in vivo that nephrin is a substrate modified by SUMO proteins thereby increasing its steady-state level and expression at the plasma membrane. A conversion of lysines to arginines at positions 1114 and 1224 of the intracellular tail of murine nephrin led to decreased stability of nephrin, decreased expression at the plasma membrane, and decreased PI3K/AKT signaling. Furthermore, treatment of podocytes with the SUMOylation inhibitor ginkgolic acid led to reduced membrane expression of nephrin. Similarly, the conversion of lysine to arginine at position 1100 of human nephrin caused decreased stability and expression at the plasma membrane. As SUMOylation is a reversible process, our results suggest that SUMOylation participates in the tight orchestration of nephrin turnover at the slit diaphragm.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Endocytosis; Glomerular disease; Glomerular filtration barrier